Potential Energy Savings and CO2 Emissions Reduction in Colombia Compressed Air Systems - Castellanos, Luis Marcos; Hernandez-Herrera, Hernan; Silva-Ortega, Jorge I.; Diaz, Vicente Leonel MartÃnez; Sanchez, Zaid GarcÃa (International Journal of Energy Economics and Policy, 2019)
Compressed air is one of the most common systems used in industry. In countries such as Australia, Italia, France, China and USA, energy consumption of compressed air systems contributes about to 10% of the total electricity consumption in industry. In Colombia, this value reaches 8%, highlighting the textile industry, with a 24% of consumption. Despite of all its advantages, compressed air is expensive, between 10-30% of consumed energy reaches the end-use point. Improvements to compressed air systems can achieve between 20-60% of energy savings, with pay-back periods lower than two years. These are the reasons that they can be considered as one of the main targetsystems while planning energy efficiency actions in industry. Colombia through different strategies has proposed to implement a group of measures to improve energy efficiency and reduce electricity consumption to 2021 around 7 %. Implementation of good practices in compressed air systems is one of them. This paper is showed the share cost, electricity consumption and the savings potential of the compressed air systems in the different divisions of the Colombian manufacturing sector, the main sectors to be involved as well as the potential savings and reduction of dioxide carbon emissions. Keywords: Compressed air systems, electricity consumption, energy efficiency. JEL Classifications: Q47, L94, N66 DOI: https://doi.org/10.32479/ijeep.8084